Metabolic intermediate acetyl phosphate modulates bacterial virulence via acetylation. Issue 1 (1st January 2019) - Ren, Jie; Sang, Yu; Qin, Ran; Su, Yang; Cui, Zhongli; Mang, Zhiguo; Li, Hao; Lu, Shaoyong; Zhang, Jian; Cheng, Sen; Liu, Xiaoyun; Li, Jixi; et al.
ABSTRACT: Accumulating evidence indicates that bacterial metabolism plays an important role in virulence. Acetyl phosphate (AcP), the high-energy intermediate of the phosphotransacetylase-acetate kinase pathway, is the major acetyl donor in E. coli . PhoP is an essential transcription factor for bacterial virulence. Here, we show in Salmonella typhimurium that PhoP is non-enzymatically acetylated by AcP, which modifies its transcriptional activity, demonstrating that the acetylation of Lysine 102 (K102) is dependent on the intracellular AcP. The acetylation level of K102 decreases under PhoP-activating conditions including low magnesium, acid stress or following phagocytosis. Notably, in vitro assays show that K102 acetylation affects PhoP phosphorylation and inhibits its transcriptional activity. Both cell and mouse models show that K102 is critical to Salmonella virulence, and suggest acetylation is involved in regulating PhoP activity. Together, the current study highlights the importance of the metabolism in bacterial virulence, and shows AcP might be a key mediator.